The Effect of Using De-contextualization and Semi-Contextualization Teaching Techniques on Turkish EFL Learners’ Vocabulary Learning - Yeganehpour, Parisa; Zarfsaz, Elham (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2022)
We are now surrounded by information from television, the internet, and digital media. Multimedia connects us to diverse languages and civilizations. The usage of a variety of forms of multimedia has a number of advantages for foreign language acquisition. The purpose of this study was to determine the extent to which using television programs and subtitled television shows as semi-contextualized strategies aids vocabulary retention during language acquisition. This research was performed at a Turkish government university. The teacher divided the classes into two experimental groups ranging in age from 18-20. The research began with the administration of a pretest. Then, the newly concentrated terms were taught using two distinct teaching techniques: decontextualized and semi-contextualized instruction. The study was conducted during a semester in 14 sessions. After teaching the new terms using the two strategies, an instant post-test was conducted at the end of sessions. A delayed post-test was conducted three sessions later. Following that, the participants' scores were statistically examined. The study's findings indicated that there were no significant differences in vocabulary teaching strategies between semi-contextualized (TV program) and decontextualized (board monitoring). It should be emphasized that the researchers, as English teacher, anticipated differences between two strategies (preference for semi-contextualized technique) based on their own teaching experience.